1999
DOI: 10.1177/0013161x99353003
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Instructional Leadership and Teacher Development: Teachers’ Perspectives

Abstract: In recent years, reflective, collaborative, inquiry-oriented approaches to supervision of teachers and teacher development have been discussed in the professional literature. However, few published studies have directly examined teachers’perspectives on principals’everyday instructional leadership characteristics and the impact of those characteristics on teachers. This article describes the everyday strategies of principals practicing exemplary instructional leadership and how these principals influenced teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
193
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(217 citation statements)
references
References 21 publications
12
193
1
11
Order By: Relevance
“…Müdür, okulun verimli olmasını sağlamak için farklı liderlik işlevleri uygular (Blasé ve Blasé, 1999, 2002Bodla ve Nawaz, 2010;Coleman, 2001;Goldring vd., 2008;Masuku, 2011). Herrera (2010) bu yaklaşıma "bana iyi bir okul gösterin, size iyi bir müdür göstereyim" (s. 5) sözleriyle katkıda bulunmuştur.…”
Section: Literatür İncelemesi öğRetimsel Liderlik Ile Okul Verimliliğunclassified
“…Müdür, okulun verimli olmasını sağlamak için farklı liderlik işlevleri uygular (Blasé ve Blasé, 1999, 2002Bodla ve Nawaz, 2010;Coleman, 2001;Goldring vd., 2008;Masuku, 2011). Herrera (2010) bu yaklaşıma "bana iyi bir okul gösterin, size iyi bir müdür göstereyim" (s. 5) sözleriyle katkıda bulunmuştur.…”
Section: Literatür İncelemesi öğRetimsel Liderlik Ile Okul Verimliliğunclassified
“…Principals have a positive impact on school culture by encouraging teacher empowerment through self-managed teacher leadership teams (Davis & Wilson, 2000;Short, 1994), encouraging teacher networking and building relationships of trust (Spillane & Thompson, 1997), engaging in specific instructional leadership practices that increase teacher motivation and self-efficacy (Basom & Frase, 2004;Blase & Blase, 1999), and sharing leadership and being open to reciprocal influences from effective teacher leaders (Anderson, 2004;Keedy & Simpson, 2001). Schools are essentially sets of interconnected relationships (Keedy & Achilles, 1997).…”
Section: Research Problemmentioning
confidence: 99%
“…To the extent that these positive effects create a greater capacity for improved student achievement, Blase and Blase (1999) concluded that the Reflective Growth Model can be a useful way to understand how principals could indirectly have a positive influence on student outcomes.…”
Section: Principal Effects On School Culture Teacher Perceptions Andmentioning
confidence: 99%
See 2 more Smart Citations